TAFSIR SURAT AL-LAHAB: ANALISIS ATAS KITAB JAMI` AL-BAYAN KARYA AL-THABARI - Muhammad Ridha (Institut Darul Quran Payakumbuh, 2016)
The Discourse of tafsir is very interesting to study and to research due because it is based on the holy Quran. Moslem experts, both mutaqaddimin and mutaakhhirin interpreted the Quran in different styles. Some experts interpreted it based on background and social life, some based on aspects of fiqh, some on language, and some others ijtima’i. As a result, the tafsir of bil-ma`tsur, the tafsir of bil-ra`y, and the tafsir of bil-isyari were produced. The purpose of the research is to discuss on imam at-Thabari and his phenomenal work, the book of tafsir at-Thabari by using the tafsir of bil-ma`tsur approach. The working mechanism is to interpret the Qur’an and Qur’an, hadiths and hadiths, and then, the ideas of colleagues and tabi’in. Besides, he also used a linguistics approach and Arabic themes. One of the Islamic experts who studies the tafsir of bil-ma`tsur is Imam at-Thabari. His complete name is Abu Ja`far Muhammad bin Jarir bin Yazid bin Khalid al-Thabari, sometimes called Yazid bin Katsir bin Ghalib. He is an Imam Mujtahid who was popular at the time. Imam at-Thabari was a Moslem expert who lived in third-century 3 in hijiriyah calendar. He was born in 221 H at Amul, the capital city of Thibristan, and died at Syawal 26, 310 H. During his life, he studied Islam with some Islam experts, like Muhammad bin Hamid al-Razi, Al-`Abbas bin Walid al-Beiruni al-Muqri, Al-Rabi` bin Sulaiman al-Muradi and another one. Some of his phenomenal and popular works are the book of Jami` al-Bayan `an-Ta`wili Ay al-Qur’an. The book is also called the tafsir of al-Thabari, the historical book of Tarikh al-Thabari, and some others.